Achievement of External Migration Goals: Empirical Analysis by a Logistic Regression Model - Boshnakov, Venelin (Research Papers, 2021)
The paper presents selected results from the analysis of primary data generated by a questionnaire survey among Bulgarian migrants conducted in 2017 after their return – temporary or permanent – to the home country. On the basis of the respondents’ statement that evaluates the achievement of their migration aims, possible interaction is explored between this achievement and the socio-economic profile of the interviewed migrants. For this purpose a binary logistic regression model has been estimated involving demographic, social, economic, and migration experience independent variables. The major results are discussed regarding the determinants of perceived achievement of migration goals by return migrants.